THE RELATIONSHIP BETWEEN THE LEVEL OF ANXIETY AND THE INCIDENCE OF DYSPEPSIA SYNDROME AMONG THE STUDENTS OF THE FACULTY OF MEDICINE AT WIDYA MANDALA CATHOLIC UNIVERSITY SURABAYA - Fellicia Stephanie Atmajaya; Rossy Sintya Marthasari; Sindrawati . (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Students’ anxiety results from multiple demands placed on them as medical students. Anxiety affects the body's functional systems, including the gastrointestinal system. Dyspepsia syndrome is one of the common symptoms.Objective: To determine whether there is a relationship between anxiety levels and dyspepsia syndrome among students at Widya Mandala Catholic University of Surabaya’s Medical Faculty.Methods: This research is an observational analytic study with a cross-sectional research design. The subjects are obtained using purposive sampling methods from the forces of 2018, 2019, 2020, and 2021. This research uses HARS questionnaires to measure anxiety levels and Rome III criteria to measure dyspepsia syndrome. Statistical analysis is performed by using Pearson Chi-Square.Result: Anxiety levels have a strong, substantial correlation with the incidence rate of dyspepsia syndrome (p=0.000). It is found that there are 4 out of 17 students (23.53%) with mild anxiety have dyspepsia syndrome, 44 out of 55 students (80%) with mild–moderate anxiety have dyspepsia syndrome, and 7 out of 8 students (87.5%) with moderate–severe anxiety have dyspepsia syndrome.Conclusion: There is a significant relationship with a positive correlation, so it can be concluded that if the level of anxiety is higher, the greater the prevalence of dyspepsia syndrome.